Effect of high-intensity anaerobic exercise on electrocortical activity in athletes and non-athletes - Élida Costa; Mariana Gongora; Juliana Bittencourt; Victor Marinho; Mauricio Cagy; Silmar Teixeira; Eduardo Nicoliche; Isabelle Fernandes; Danilo Fagundes; Caroline Machado; Juliana Dias; Renan Vicente; et al. (PLoS ONE, 2025)
Aim The present study aims to verify the information processing in athletes through electroencephalography, analyze cortical areas responsible for cognitive functions related to attentional processing of visual stimuli, and investigate motor activity’s influence on cognitive aspects. Additionally, we aimed to analyze the acute effect of physical exercise after the high-intensity anaerobic effort, evaluating how a short-duration Wingate test influences cortical activity and attentional processing immediately following exertion. Materials and methods The sample consisted of 29 subjects, divided into an experimental group (n = 13 modern pentathlon athletes) and a control group (n = 16 non-athletes). We collected the electrocortical activity before and after the Wingate Anaerobic Test. During the electrophysiological measures, the volunteers performed a saccadic eye movement paradigm. They also performed cognitive tasks, resting heart rate, and anthropometric measurements. Results A mixed ANOVA was applied to analyze the statistical differences between groups (athletes and control) and moments (before and after exercise) for F3, F4, P3, and P4 electrodes during rest one and task (pre-stimulus GO). There was an interaction for the group vs. moment factors in F3 [F = 17,129; p = 0,000; η² = 0.512], F4 [F = 22,774; p = 0,000; η² = 0.510], P3 [F = 11,429; p = 0,001; η² = 0.405], and P4 electrodes [F = 18,651; p = 0,000; η² = 0.379]. We found the main effect for group factors in the frontal and parietal electrodes of the right hemisphere (F4 and P4) and a main effect of the moment factor on the frontal (F3 and F4) and parietal (P3 and P4) electrodes. There was an interaction between the group vs. moment factors for the reaction time. The groups were different in Peak Power (Watts/kg), Average Power (Watts/kg), Fatigue Index (%), and Maximum Power (ms). Conclusions We identified chronic effects of exercise training on the cortical activity of modern pentathlon athletes, read-through differences in absolute alpha power, and acute effects of a high-intensity exercise session for athletes and non-athletes for electrocortical and behavioral responses.